The Willed Body Donor Interview project: Medical student and donor expectations. Issue 2 (26th October 2012) - Bohl, Michael; Holman, Alexis; Mueller, Dean A.; Gruppen, Larry D.; Hildebrandt, Sabine
Abstract The Anatomical Donations Program at the University of Michigan Medical School (UMMS) has begun a multiphase project wherein interviews of donors will be recorded and later shown to medical students who participate in the anatomical dissection course. The first phase of this project included surveys of both current UMMS medical students and donors concerning their perceptions of such a program. A five‐question survey administered via Qualtrics software was electronically mailed to all current medical students at UMMS, and a survey was mailed to registered and potential donors requesting information from the UMMS on anatomical donations. A total of 224 medical student responses (response rate 33%) and 54 donor responses (response rate 27%) were received. Seventy‐four percent of students and 81% of donors reported they would participate in this program if it existed. Students and donors supported the implementation of this program for varying reasons, though many felt strongly they would not want to participate in a donor interview program. These qualitative results support those of previous studies that show a majority of students desire a closer personal relationship with the donor, and these are the first results to be reported on donor perceptions of a donor interview program. Although many students and donors are in favor of instituting this program, others feel strongly that such an experience could be traumatic. The causes of these differing reactions need to be further explored, and the opinions of those who object to this study will be respected by maintaining voluntary participation in future phases of this study. Anat Sci Educ 6: 90–100. © 2012 American Association of Anatomists.